RELIGIUSITAS DALAM NASKAH DRAMA “SKETSA-SKETSA DI KEBUN WARISAN” KARYA RACHMAT HIDAYAT MUSTAMIN - Shilpa Nuraini; Yusra Dewi; Ade Bayu Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze religiosity in the drama script Sketsa-Sketsa di Kebun Warisan by Rachmat Hidayat Mustamin using a sociology of literature approach. Religiosity is understood as a multidimensional phenomenon that is not limited to religious beliefs and practices, but also includes inner experiences, value-based knowledge, and the behavioral implications of characters within a social context. This research employed a descriptive qualitative method, with data sources consisting of dialogues and narrative elements in the drama script. Data were collected through library research using reading and note-taking techniques, while data analysis was conducted through content analysis based on five dimensions of religiosity, namely belief, religious practice, religious feelings, religious knowledge, and religious effects. The results show that religiosity in the drama script Sketsa-Sketsa di Kebun Warisan is represented holistically and contextually through all five dimensions. Religious feelings emerge as the most dominant dimension, followed by belief and religious effects, while religious practice and religious knowledge appear implicitly. The characters’ religiosity is not presented in a normative-dogmatic manner, but rather as an existential response to agrarian conflict, structural pressure, and social trauma. These findings indicate that religiosity in the drama functions as a source of meaning, moral resilience, and social awareness. This study contributes theoretically to the field of religious literary studies by offering a contextual and multidimensional analysis, and practically by providing insights that can be utilized as teaching material for literature learning oriented toward value formation and social understanding.